Risk for the surgical team during orthopaedic surgeries - Sah, Shambhu; KC, Bikash; Dangi, Sailoj Jung; Khanal, Kanak; Basnet, Ramesh (Journal of Society of Anesthesiologists of Nepal, 2017)
Orthopaedic surgeons and the surgical team not only face health hazards faced by most of the physicians in any medical field but also hazards specific to the practice of orthopaedic surgery. Common health hazards are related to radiation, infections, surgical smoke, noise, chemicals, physical and it may be psychological. The aim of this article is to review the hazards and raise the awareness for the safety of orthopaedic surgeon and the surgical team as well as patient and newly introduced surgical team member in Operation Theater.